The role of parents in the motivation of young athletes: a systematic review - Gao, Z.; Chee, C. S.; Wazir Norjali Wazir, M. R.; Wang, J.; Zheng, X.; Wang, T. (Frontiers in Psychology, 2023)
Objectives Parents are one of the main social agents that shape young athletes` experiences and participation in sports, but they are also the least explored group in the literature. Therefore, the purpose of this study was to conduct a systematic review of research on the role of parents in the motivation of young athletes.